The pseudoenzyme ADPRHL1 affects cardiac function by regulating the ROCK pathway - Lei Tian; Tianwei Guo; Fujian Wu; Rui Bai; Sinan Ai; Hongyue Wang; Yuanxiu Song; Min Zhu; Youxu Jiang; Shuhong Ma; Xiaofeng Zhuang; Shuzhen Guo (Stem Cell Research & Therapy, 2023)
Abstract Background Pseudoenzymes, catalytically deficient variants of active enzymes, have a wide range of regulatory functions. ADP-ribosylhydrolase-like 1 (ADPRHL1), a pseudoenzyme belonging to a small group of ADP-ribosylhydrolase enzymes that lacks the amino acid residues necessary for catalytic activity, may have a significant role in heart development based on accumulating evidence. However, the specific function of ADPRHL1 in this process has not been elucidated. To investigate the role of ADPRHL1 in the heart, we generated the first in vitro human embryonic stem cell model with an ADPRHL1 knockout. Method Using the CRISPR/Cas9 system, we generated ADPRHL1 knockout in the human embryonic stem cell (hESC) H9 line. The cells were differentiated into cardiomyocytes using a chemically defined and xeno-free method. We employed confocal laser microscopy to detect calcium transients and microelectrode array (MEA) to assess the electrophysiological activity of ADPRHL1 deficiency cardiomyocytes. Additionally, we investigated the cellular mechanism of ADPRHL1 by Bulk RNA sequencing and western blot. Results The results indicate that the absence of ADPRHL1 in cardiomyocytes led to adhered abnormally, as well as perturbations in calcium transients and electrophysiological activity. We also revealed that disruption of focal adhesion formation in these cardiomyocytes was due to an excessive upregulation of the ROCK–myosin II pathway. Notably, inhibition of ROCK and myosin II effectively restores focal adhesions in ADPRHL1-deficient cardiomyocytes and improved electrical conduction and calcium activity. Conclusions Our findings demonstrate that ADPRHL1 plays a critical role in maintaining the proper function of cardiomyocytes by regulating the ROCK–myosin II pathway, suggesting that it may serve as a potential drug target for the treatment of ADPRHL1-related diseases.